The BA in the Internet, Learning and Organizations: A peer to peer approach to distance learning - Holyfield, Sarah; Liber, Oleg; Richardson, Paul; Smart, Christina (Proceedings of the International Conference on Networked Learning, 2002)
This paper provides an account of the use of Colloquia, a peer-to-peer learning environment, to deliver a new distance learning, parttime degree at Bangor, the BA Internet, Learning and Organizations. Colloquia is a personal application, running on each student’s or teacher’s machine, it is not a server-based environment. The paper describes the educational and organizational theories and rationale behind the development of both the environment and the degree itself, the way it is taught, and progress over the first semester. Participation levels have been high along with the formation of a very positive group identity and reasons for this are explored.